EL GENERO AMPHIGRAPTUS LAPWORTH (GRAPTOLITHINA) EN EL ORDOVICICO ARGENTINO (Ameghiniana, 2013)
A graptolite of the genus Amphigraptus Lapworth from the lower levels of the caradocian sequence exposed at San Isidro, Mendoza, is described. The fossil-bearing strata are ascribed to the Zone of Nemagraptus gracilis.